2017
DOI: 10.1080/15622975.2017.1372629
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing of bipolar disorder lymphoblastoid cell lines implicates the neurotrophic factor HRP-3 in lithium’s clinical efficacy

Abstract: We observed higher expression levels of HDGFRP3 and ID2 in BD patients who favourably respond to lithium. Both of these genes are involved in neurogenesis, and HDGFRP3 has been suggested to be a neurotrophic factor. Additional studies in larger BD cohorts are needed to confirm the potential of HDGFRP3 and ID2 expression levels in blood cells as tentative favourable lithium response biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 78 publications
2
25
1
Order By: Relevance
“…However, ID2 expression was higher in PBMC from LNR compared with LR BD patients (Figure a; FD = 4.5, p = .0297). This finding is the opposite of what we expected based on our RNA‐sequencing study in LCLs (Milanesi et al, ). The reasons for this difference are unclear, and may reflect the fact that the majority of cells in the PBMC fraction are T lymphocytes while LCLs are derived from B lymphocytes (Ryan et al, ).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, ID2 expression was higher in PBMC from LNR compared with LR BD patients (Figure a; FD = 4.5, p = .0297). This finding is the opposite of what we expected based on our RNA‐sequencing study in LCLs (Milanesi et al, ). The reasons for this difference are unclear, and may reflect the fact that the majority of cells in the PBMC fraction are T lymphocytes while LCLs are derived from B lymphocytes (Ryan et al, ).…”
Section: Resultscontrasting
confidence: 99%
“…We recently reported, based on a genome‐wide RNA‐sequencing study, that two protein coding genes, the transcription factor ID2 (inhibitor of DNA binding 2) and HDGFRP3 (hepatoma‐derived growth factor, related protein 3), showed differential expression when comparing the transcriptome of lymphoblastoid cell lines (LCLs) from LR and LNR BD patients (Milanesi et al, ). Both genes had higher expression in LCLs from BD patients who favorably responded to lithium (Alda scale >6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of a neuronally-relevant module (Magenta) is notable because LCLs are non-neuronal cells. While other LCL-based studies of psychiatric disease identified individual genes of potential neuronal relevance [ 26 29 ], with others leveraging WGCNA to implicate non-specific cellular or immunologic modules [ 30 32 ], this is the first study using LCLs to implicate a neuronally-relevant module in psychiatric disease. In a preliminary analysis, Magenta hub genes were enriched for targets of REST , a repressor of neuronal genes in non-neuronal cells [ 17 ], suggesting that despite mechanisms limiting neuronal gene expression such as REST -mediated transcriptional repression, potentially meaningful differences in aggregate expression could still be detected, perhaps due to careful phenotyping and appropriate clinical stratification.…”
Section: Discussionmentioning
confidence: 99%
“…The data for the second cohort were taken from the published work of Milanesi et al 37 and consisted of 12 BD LR and 12 BD NR patients.…”
Section: Second Cohortmentioning
confidence: 99%